Assessing Economic Diplomacy : Bilateral Trade and Investment Relations between Kazakhstan and EU - Schleimer, Alexandra; Zeynalov, Ayaz; Mammadov, Orkhan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
In today's globalized world, the importance of bilateral relations between countries is continually increasing. The partnership between Kazakhstan and the European Union (EU) is an illustrative example of strong cooperation based on shared economic and political interests, supported by effective economic diplomacy. The aim is to explore the strategic use of economic diplomacy as a basis for maintaining strong bilateral relations. Kazakhstan's strategic location and abundant resources have attracted close attention, leading to active cooperation with Western partners, particularly the EU in trade and foreign direct investment (FDI) domains. One of the core research objectives is to explore how cooperation affects Kazakhstan's economic diversification and the EU's energy security. Moreover, the study investigates how long-term relations between the partners have evolved under conditions of geopolitical shifts and economic fluctuations. A Gravity Trade Model approach using global statistical data for the period from 1995 to 2021 was applied for this purpose. The study aims to identify the vital factors that underpin long-term cooperation. The results emphasize the significant impact of GDP, oil prices and geopolitical shifts on bilateral trade between Kazakhstan and the EU. Despite challenges such as the COVID-19 pandemic and geopolitical tensions, economic diplomacy has facilitated continuous cooperation, demonstrating the sustainability of the partnership between Kazakhstan and the EU. Moreover, the analysis reveals a pattern of mutual dependence: Kazakhstan relies on EU investment inflows and the EU relies on Kazakhstan's abundant resources.
Vedoucí práce: Ayaz Zeynalov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor bakal. práce]; bakalářské práce; bachelor's theses